KINERJA PERUSAHAAN PERBANKAN (STUDI PERBANDINGAN DUA PERIODE KRISIS DI INDONESIA) - Halim, Edyanus Herman (Jurnal Tepak Manajemen Bisnis, 2014)
The purpose of this study was to determine whether there are differences in the Capital Adequacy Ratio(CAR), Net Interest Margin (NIM), Net Profit Margin (NPM), Return on Assets (ROA), Operating Expenses toOperating Income (ROA), Loan to Deposit Ratio (LDR), and stock returns in the two periods of crisis in Indonesia.Namely the 1997 and 2008 samples in this study were all from the years 1993 to 2010 the banking company. Thedata analysis technique used in this study using a different test (t test).There are four hypotheses to be tested in the research ini. testing shows that for the variable CAR, NIM, NPM,ROA, ROA, and LDR there are differences in the performance of the company before the crisis of 1997 with theperformance of the company after the 1997 crisis, while, from the test results for the variable return stock showsthat there is no difference stock returns before the 1997 crisis after the 1997 crisis results show that there aredifferences in LDR and stock returns before the banking crisis of 2008 and after the 2008 crisis, while, from theresults of the test there was no difference before the 2008 crisis and post-crisis 2008 for the variable CAR, NIM,NPM, ROA, and BOPO.Hasil testing shows that there are differences in NIM, NPM, ROA, LDR and bankingcompany stock returns before the crisis before the crisis of 1997 and 2008, while, from the results of the test therewas no difference in the pre-crisis before the crisis of 1997 and 2008 for variable CAR and ROA. testing showsthat there are differences in the CAR, NIM, NPM, ROA, ROA, and stock returns after the banking crisis of 1997and after the crisis of 2008, while, from the results of the test there was no difference in post-crisis after the crisisof 1997 and 2008 for variable LDR.Keywords : Camel, Economic CrisisI.